2022
DOI: 10.1111/jcmm.17305
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PD‐L1 causes germ cells to slough from mouse seminiferous tubules via the PD‐L1/PD‐L1 interaction

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…In this study, combined with previous studies that found that PD-L1 can bind to PD-L1 to cause cell detachment, 7…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…In this study, combined with previous studies that found that PD-L1 can bind to PD-L1 to cause cell detachment, 7…”
Section: Discussionsupporting
confidence: 58%
“…We transfected SW480 cells with PD‐L1‐HA expression lentivirus, and the mRNA and protein levels of PD‐L1 substantially increased in PD‐L1 expression lentivirus‐transfected SW480 cells (Figure 2C,D), and PD‐L1 was mainly localized to the cell membrane by immunocytochemistry assay (Figure 2F). We found that PD‐L1 with HA in CRC cells could bind to PD‐L1 with FLAG (Figure 2E), and in a previous study we found that PD‐L1 interacted with PD‐L1 to cause cell shedding 7 . Then, we investigated the effect of PD‐L1/PD‐L1 on the migration of CRC cells.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations